The use of the assessment portafolio to promote the 21st century skills (collaboration communication and critical thinking ) Focused on writing in the students of second year of bachillerato Degree at Ecológico Trilingue Gonzalo Ruales Benalcázar High school during the school year 2013-2014 - Caizaluisa Cárdenas, Valeria Pilar (2014)
This research was carried out in order to promote the use of the assessment portfolio to develop the 21st century skills (collaboration, communication and critical thinking) focused on writing among the students of "Ecológico Trilingüe Gonzalo Ruales Benalcázar" high school located in Conocoto in the period September 2013- January 2014. After making a previous diagnosis of the advance of these students in the subject of English, it was found out that they were involved in a very monotonous learning English process with a minimum of participation, not any practice of collaborative work, or critical thinking and what is worse, Spanish translation was used when using their English in class.